دور ديوان الزكاة في تعزيز أنشطة المويل الأصغر وتخفيف حدة الفقر في السودان : الممكن والمأمول من برنامج الإغناء بالزكاة - حسن البصري، محمد الامين تاج الاصفياء (جامعة الجزيرة - عمادة الدراسات العليا والبحث العلمي, 2011)
تتعالى من حين لآخر دعوات تنادي بضرورة أن يسهم ديوان الزكاة في التصدي لمشكلة الفقر في السودان من خلال المساهمة في توفير التمويل الأصغر للمشروعات الصغيرة التي يملكها الفقراء، أو تمليك مثل تلك المشروعات للفقراء النشطين اقتصاديا. لكن مثل هذه الدعوات تغفل عن حقيقة أن تقويم تجربة ديوان الزكاة في السودان في هذا المجال تكشف عن فجوة كانت وما تزال تتسع بين ما يأمل فيه الناس من ديوان الزكاة وما يمكن أن يقدمه الديوان وفق معطيات الفقه والتشريع الذي يحكم عمله، إلى جانب المحددات الأخرى التي يعمل الديوان في إطارها. من هنا تهدف هذه الدراسة إلى استقراء دور ديوان الزكاة في تعزيز أنشطة التمويل الأصغر من خلال برامج الإغناء بالزكاة، وإمكانية مساهمته من خلال مثل هذه البرامج في التخفيف من حدة الفقر في السودان. وقد انتهجت الدراسة في سبيل ذلك نهجا يقوم على مقارنة ما تنادي به دعوات المتطلعين إلى دور أكبر للديوان في هذا المجال وما انتهت إليه الدراسات العملية والمسحية من حقائق الواقع حول ما يقوم به الديوان فعلا. وخلصت الدراسة في هذا الخصوص إلى أن الفجوة ما تزال عظيمة بين ما هو مأمول من الديوان وما هو متحقق على أرض الواقع، وأن هناك معوقات عدة تحول ما بين ديوان الزكاة في السودان والدور المرتجى منه في التصدي لمعضلة الفقر من خلال آلية التمويل الأصغر عموما وبرامج الإغناء بالزكاة تحديدا.
Calls were increasingly made now and then for the Zakah Chamber to take part in the efforts made to alleviate poverty in the Sudan through the provision of microfinance to the small projects owned by the poor and needy, or through allotting funds for those economically active poor individuals mainly as part of the enrichment through Zakah programs. Such calls seem to be a bit unwary of the fact that the experience of the Zakah Chamber in this regard leaves much to be wanted in the light of the rulings governing the activities of the Chamber, together with the many other limitations imposed upon it. This paper attempts to establish through an inductive comparative reasoning the role of the Zakah Chamber in the elevation of microfinance activities as part of its contribution to the efforts made to alleviate poverty in the Sudan by enriching the poor and needy active individuals and families. A comparison is made between, on the one hand, the calls made by those aspiring for a greater role for the Chamber in this regard, and on the other hand the realities captured by many empirical and survey studies. The most important conclusions reached by the paper were that, when it comes to people's expectations, the gap still remains very wide and is indeed getting wider by the day between what people are hoping for and what the Chamber can do, and that there are a number of constraints limiting the role of the Zakah Chamber in the alleviation of poverty in the Sudan through the mechanism of microfinance generally or indeed through the enrichment through Zakah programs in particular.
Keywords: السودان -- الزكاة -- التمويل الأصغر -- الحد من الفقر -- التنمية الاجتماعية